Penerapan Model Dialog Sebagai Jembatan Pelaksanaan Misi - Baginda Sitompul; Halima Marisa Nababan; Irene Tampubolon; Simon Simbolon; Yanti Panggabean; Nadia Sitanggang (Student Scientific Creativity Journal, 2024)
The study of dialogue in the context of pluralism of religions (multi-religious), which is also linked to the implementation of missions or preaching in religions, is not a new issue in the study of theology and the study of religions; considered by the author to be important to continue to study. The reason why dialogue linked to mission is being discussed at this time is firstly, dialogue that assumes acceptance between fellow religious believers displays the murky reality of harmonious relations between religious believers. Good dialogue to be developed by religious communities is dialogue of action and dialogue of life as a form of dialogue that is correlational and globally responsible. Second, Christian mission can be understood as an effort to lift humanity from its downturned reality.